Otomotiv Yan Sanayisinde Malzeme Besleme Sisteminin Yalın Üretim Yaklaşımıyla Yeniden Tasarlanması Ve Bir Uygulama - Uçan, Kıraç (Fen Bilimleri Enstitüsü, 2014)
20. yüzyılın başlarından itibaren hızla gelişen endüstriler süreçlerini daha iyi kontrol etmek ve maliyetlerini azaltmak istemektedirler. 1960’lı yıllarda Toyota Motor Company tarafından uygulanmaya başlanan ve 1974 yılında dünyayı sarsan petrol krizi ile beraber “Yalın Üretim Sistemi” tüm dikkatleri üzerine çekmiştir. Yalın üretim sisteminin temeli sıfır hata ve sıfır stok prensibine dayanmaktadır. Yalın üretim sistemine göre müşterinin para ödemek istemeyeceği her aktivite israftır. İsraflar, yalın üretim sistemindeki araçlar kullanılarak ortadan kaldırılabilir veya azaltılabilir. Böylece işletmeler için maliyete neden olan ama katma değer yaratmayan aktiviteler yani israflar ortadan kalkar ve işletmelerin rekabet güçleri artar. Bu çalışmada, yalın üretim yaklaşımının nasıl ortaya çıktığı, yalın üretim sisteminin tanımı ve amacı açıklanmıştır. Yalın üretim sistemi bakış açısıyla işletmelerdeki israfların türleri ve oluşum nedenleri belirtilmiştir. Yalın üretim sisteminin uygulanması için işletmenin sahip olması gereken ilkeler belirtilmiştir. Üretim kontrol ve malzeme tedariğine ilişkin yalın üretim tekniklerinden çekme sistemi, süreç içi sabit stok, polca, kit halinde teslimat, döngüsel sefer ve karma sistemler detaylı olarak incelenmiştir. Otomotiv yan sanayisinde iklimlendirme sistemleri alanında uluslararası faaliyet gösteren bir işletmede uygulama yapılmıştır. İşletme, Türkiye ve Almanya fabrikasında ürettiği klimalarda kullanılan bakır boruları firma bünyesinde üretmektedir. İşletmedeki tüm üretim bölümlerinin kontrolü üretim planlama bölümü tarafından yapılmaktadır. Yarı mamul olan bakır borular, malzeme tedariğine ilişkin yalın üretim teknikleri kullanılarak incelenmiş ve üretim planlamadan bağımsız olarak kendi üretim ihtiyacını kontrol eden bir yapıya dönüştürülmesine karar verilmiştir. Bir üründe yaklaşık on farklı tipte bakır boru kullanılmaktadır. Yapılan çalışma sonucunda aynı üründe gereksinim duyulan borular kit haline getirilmiştir. Her bir kitin bir ürünlük malzeme bulundurması gerekmekte fakat bu durum üretim süreci açısından probleme sebep olmaktadır. Bu kitler için kanban büyüklükleri belirlenerek tek kanbanlı sistem uygulanmıştır. Almanya fabrikası için üretilen boruların belli bir sipariş yoğunluğuna sahip olanları için tek kanbanlı sistem, bu yoğunluğun altında kalan boruların ise POLCA sistemine benzer bir sistem ile takip edilmesine karar verilmiştir. Yapılan uygulama sonucunda ek alan ve maliyete gereksinim duyulmadan, malzeme tedariği, malzeme kontrolü ve üretim talebi kontrolünde %51 ile %100 arasında değişen iyileştirmeler olmuştur. Stoklardan yaklaşık %2 artış olmuştur. Bu artış yönetim tarafından kabul görmüştür. Üretim planlama bölümünden kaynaklanabilecek hatalar ortadan kaldırılmıştır. Klima üretim hattı ile bakır boru üretim tesisi arasında üretim kontrol ve malzeme besleme sistemi geliştirilmiştir. Borular kit olarak kullanılmakta ve kullanım sonrasında sistemde ihtiyaç fazlası boru kalmamaktadır. Kit halinde teslimat yapılan uygulamalarda depoda kitler çalışanlar tarafından hazırlanırken, bu uygulamada bakır boru üretiminin boruları kit haline getirilmiş şekilde üretmesi sağlanmış ve kit hazırlama maliyeti oluşmamıştır.

Beginning of 20th century demand of the market had increased. Companies wanted to increase their production speed. Therefore, mass production method was become the best production method. While after production rate was caught the demand, customers were wanted to have the products customized and affordable price. Rapid growth industries want to control and reduce their costs. Lean Manufacturing System was applied by Toyota Motor Company in the 1960’s. In 1974, oil crisis arises and calls attention to Lean Manufacturing System. The main aim of this system is meeting the customer demand with using minimum sources. Lean manufacturing system is based on two principles, which are zero failure and zero stock. Every activity which customer isn’t willing to pay is waste. These wastes could be eliminated or reduced by using Lean manufacturing tools. Most known seven wastes are over production, waiting, carrying, processing wastes and working with huge stock, movements and defective products. Activities, which have non value adding costs in other term wastes, are removed and company opportunities are increased. In this thesis, how lean manufacturing was showed up, definition and goals of the lean manufacturing system are explained. Types of waste and causes are described from lean manufacturing aspect. The mandatory principles in order to apply lean manufacturing system are defined. Four principles which are value, value flow, flow and pull, have to be applied first. Afterwards, zero defect aspect has to be applied. In the literature research, types of pull system, constant work in process, paired-cells overlapping loops of cards (POLCA), kitting, milk-run and production control and hybrid systems are studied in detail with figures. Especially, pull system, POLCA and kitting and their interaction are researched. Pull system and kitting were used in many cases regarding to automotive sector. Reasons of these are high handling costs, space requirements, having high customization requests. An application is done in a factory which produces air conditioning units as a original equipment manufacturer in automotive industry. Factory produces their units to order. This factory produces air conditioning units to sell and produces copper pipes and light resin transfer molding covers in order to install their end products. Copper pipes and covers are in-house production and they are used in both Turkey and Germany plants. Copper pipe production is located three kilometers away from the factory Therefore, logistics costs were taken into consideration. In the thesis, actual order acceptance process and production processes are explained by using value stream mapping method. Afterwards, production planning system for both air conditioning and copper pipe production are explained in detail. Light resin transfer molding production is left out of the scope. In actual state, production plan for each production department is given by production planning department. Material feeding systems for copper pipes, which are used in both Turkey and Germany plant, were researched. Potential problems and disadvantages of actual system were examined. Material feeding system requires high work forces of warehouse employees. Produce to order systems requires more setup times. In addition, approximately on different shaped copper pipes are assembled while a unit is producing. Therefore, production can’t be done because of partial production. While redesigning the material feeding system pipes for Turkey plant and Germany plant are separated. The pipes, which are going to be consumed in Turkey plant, become a kit. These kits are created according to pipe-unit matrix. Actually, kits must be consisted of the pipes which are used in same units. Normally, parts in one kit should belong to one unit, but in this application these kits are turned into one bin kanban system due to production restrictions. By this way, setup times and kit preparation times are decreased. Thereafter, pipe production foremen can be able to give a decision of what should be produced. Production planner was giving the production quantities according to system but here after foremen also see the physical situation. Due to having discrete manufacturing, number of Kanban’s must be at least two. Because of that, number of Kanban calculation formula was converted to quantity per kanban equitation whose unknown is quantity per kanban. Required carrier options are searched. Three different types of carriers are used in actual state. Copper pipes for the Germany plant are separated into two different groups. One bin kanban systems were applied to the higher demand group. Lower demand group will have a system similar to POLCA. Higher demand group is consisted of 39 different material codes whose average demands are higher than 20 pieces per month. Lower demand group is consisted of 120 different material codes are lower than 20 pieces per month. Kanban system for higher demand group is exactly same with Turkey plant kanban system. Requirements regarding to Turkey plant are controlled by pipe production foremen. Not only systemic but also physical control is established. Stocks out costs are reduced due to using of kanban system. Pipes are become kit and partial production problems are solved. Work forces for checking the parts availability are improved %100. Material supplies to the production line are done by warehouse employee. Materials are supplied by kits therefore material feeding time is reduced by %80. Control of production requirements are reduced by %72. Control of production requirements for Germany plant is reduced by %57. Existing material carriers are used in future state. Existing material stocking area is efficiently used and layout study is done. Improved value stream map for pipe production is drawn. Production plan flow between production planning and copper pipe production foremen is removed. As a result, stocks are increased by %2. Management accepted this increasement in stocks. All mistakes could be done by production planning are eliminated. Self-control mechanisms are created. Material feeding system has established between air conditioning production line and copper pipe production line. Normally, kitting workers are required for kit preparation in general. However, in this application, kits are prepared by pipe production employees during while pipes are producing. Existing material carriers and existing stocking areas are used efficiently. Setup times are reduced due to producing as many as kanban quantities.
Redesigning Of Material Feeding System With Lean Manufacturing Point Of View And An Implementation In Automotive Industry
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2014
Keywords: Yalın Üretim; kanban; kit halinde teslimat; POLCA; malzeme besleme sistemleri; lean manufacturing; kanban; kitting; POLCA; material feeding systems